The Orphan Crop Crassocephalum crepidioides Accumulates the Pyrrolizidine Alkaloid Jacobine in Response to Nitrogen Starvation - Schramm, Sebastian; Rozhon, Wilfried; Adedeji-Badmus, Adebimpe N.; Liang, Yuanyuan; Nayem, Shahran; Winkelmann, Traud; Poppenberger, Brigitte (Frontiers in Plant Science, 2021)
Crassocephalum crepidioides is an African orphan crop that is used as leafy vegetables and medicinal plant. Although it is of high regional importance in Sub-Saharan Africa, the plant is still mainly collected from the wild and therefore efforts are made to promote its domestication. However, in addition to beneficial properties, there was first evidence that C. crepidioides can accumulate the highly toxic pyrrolizidine alkaloid (PA) jacobine and here it was investigated, how jacobine production is controlled. Using ecotypes from Africa and Asia that were characterized in terms of their PA profiles, it is shown that the tetraploid C. crepidioides forms jacobine, an ability that its diploid close relative C. rubens appears to lack. Evidence is provided that nitrogen (N) deficiency strongly increases jacobine in leaves of C. crepidioides, that this capacity depends more strongly on the shoot than the root system, and that homospermidine synthase (HSS) activity is not rate-limiting for this reaction. A characterization of HSS gene representation and transcription showed that C. crepidioides and C. rubens possess two functional versions, one of which is conserved, that the HSS transcript is mainly present in roots and that its abundance is not controlled by N deficiency. In summary, this work improves our understanding of how environmental cues impact PA biosynthesis in plants and provides a basis for the development of PA-free C. crepidioides cultivars, which will aid its domestication and safe use